EARLY OUTCOME OF MEATAL MOBILIZATION TECHNIQUE FOR DISTAL HYPOSPADIAS: BASED ON 5 YEARS’ EXPERIENCE IN A PEDIATRIC SURGERY CENTRE-SHAR HOSPITAL-SULAIMANI CITY-KURDISTAN REGION-IRAQ - Marif, Mahdi Aziz Hama (Journal of Sulaimani Medical College, 2020)
Background Hypospadias is a challenging field of urogenital reconstructive surgery with different techniques being currently used. Numerous reconstruction techniques have been described previously; none can be used to correct all forms of hypospadias. The ideal result of surgery is the construction of a good caliber urethra with a slit-like urethral meatus at the tip of the glans and a straight penis. Objectives Assessing the early outcome of the meatal mobilization technique for repairing distal hypospadias regarding parent’s satisfaction for the cosmetic appearance of glans, position of the meatus, and urine stream. Patients and Methods The work approved by the ethics committee of the College of Medicine – University of Sulaimani (no.5, on 19/2/2019). Sixty male children enrolled in the pediatric surgery center in Shar hospital/ Sulaimani city /Kurdistan region-Iraq in the period of 5 years from July first, 2013 to June 30th 2018. Informed consent was taken from the parents in the form of face to face interview in the Kurdish language; for discussion of the options of treatment and possible complications. All the patients were followed up, weekly in the first month and monthly in the first 6 months, and yearly there after postoperatively. Results Patients enrolled in the study their age ranged from 6 months to 7 years, most of them were from the age group 7-12 months. The second and third age group were (13-18 months), (19-24 months) respectively. The most common complication following hypospadias repair by meatal mobilization technique (MEMO) technique was meatal stenosis (n=3, 5%) followed by urethrocutaneous fistula, breakdown requiring re-do surgery, and urethral stricture (n=2, 3.33%) (n=2, 3.33%) (n=1, 1.66%) respectively. The majority of the patient’s parents were satisfied with the result of the repair, regarding the position of the opening, cosmetic appearance, and urine stream. While satisfaction among the parents concerning the stream of the urine was (n=54 90%). Conclusion Meatal Mobilization Technique is a relatively safe and effective procedure for correction of all types of distal hypospadias including glandular, coronal, and subcoronal variants.it is associated with a minimal complication rate and a good parental satisfaction rate regarding the cosmetic appearance and urine stream.
Keywords: Distal hypospadias; Hypospadias; Meatal mobilization outcome; Parental satisfaction